Oscillatory Properties Test for Even-Order Di§erential Equations of Neutral type (European Journal of Pure and Applied Mathematics, 2023)
This paper presents a study on the oscillatory behavior of solutions to even-order neutral differential equations involving p-Laplacian-like operator. We obtain oscillation criteria using techniques from first-order delay differential equations, Riccati technique and integral averages technique. The results of this work contribute to a deeper understanding of even-order differential equations and their connections to various branches of mathematics and practical sciences. The findings emphasize the importance of continued research in this area.
Keywords: Oscillation conditions, neutral, even-order, di§erential equations